The Effect of Net Profit Margin (NPM) and Current Ratio (CR) on Profit Growth - Megawati Megawati; Ayke Nuraliaty; Indri Utami (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the effect of Net Profit Margin (NPM) and Current Ratio (CR) on profit growth in retail trade sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. This research employs a quantitative approach. The sampling technique used in this study is purposive sampling, resulting in 13 companies that meet the specified criteria. The analytical method applied in this research is panel data regression analysis using EViews 12 software. The results indicate that partially, Net Profit Margin (NPM) has a positive and significant effect on profit growth, while Current Ratio (CR) has a negative and significant effect on profit growth.